PERBANDINGAN KEUANGAN BERDASARKAN TEORI-TEORI LABA SECARA KUALITATIF - Ahmad Rasyiddin; Budi Dharma; Febri Sari Siahaan (Universitas Tangerang Raya, 2022)
Financial profit is closely related to the company's valuation which is presented by the stock price. Earnings information is one of the instruments used by investors in making investment decisions. Significant relationship between the company's earnings announcements with changes in stock prices and earnings levels. but earnings information alone is not enough to serve as a basis for decision making by investors, because the information is very limited and sometimes provides biased information. Based on the background described above, several problems can be formulated as follows: Does the current tax burden affect earnings management practices in companies in the consumer goods industry sector in the food and beverage sub-sector listed on the Indonesia Stock Exchange, Does tax planning affect practice? earnings management in consumer goods industrial sector companies in the food and beverage subsector listed on the Indonesia Stock Exchange?. The results showed that.There are many experts who define profit including those from the Indonesian Institute of Accountants (IAI), the Financial Accounting Standards Board (FASB). From these many opinions it can be concluded that profit is derived from income after deducting the costs incurred in the company's operational activities. The theories that support profit are the risk-bearing theory of profit, the theory of profit, the innovation theory of profit and the managerial efficiency theory of profit. While the measurement of profit is the determination of the rupiah amount of profit recorded and presented in the financial statements.